Secondary battery

The integration of a zincate ion supply body with zinc oxide or zinc hydroxide in the secondary battery addresses the challenges of dendrite growth and hydrogen generation, significantly enhancing the charge/discharge cycle characteristics and overall battery performance.

JP7657554B2Active Publication Date: 2025-04-07MAXELL LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020138557
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-23
Filing Date
2020-08-19
Publication Date
2025-04-07
Estimated Expiration
2040-08-19

AI Technical Summary

Technical Problem

Secondary batteries with zinc poles face challenges in maintaining charge/discharge cycle characteristics due to issues like dendrite generation, hydrogen gas production, and passivation, which affect the battery's capacity and lifespan.

Method used

The secondary battery incorporates a negative electrode made of zinc oxide, along with a zincate ion supply body containing zinc oxide or zinc hydroxide, which is not electrically connected to the electrodes. This configuration helps in suppressing dendrite growth and hydrogen generation, thereby enhancing the charge/discharge cycle characteristics.

Benefits of technology

The use of a zincate ion supply body with zinc oxide or zinc hydroxide in the secondary battery effectively improves the charge/discharge cycle characteristics by preventing dendrite growth and hydrogen generation, leading to a more stable and longer-lasting battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657554000001
    Figure 0007657554000001
  • Figure 0007657554000002
    Figure 0007657554000002
  • Figure 0007657554000003
    Figure 0007657554000003
Patent Text Reader

Abstract

To provide a secondary battery superior in charge / discharge cycle characteristic, and having a negative electrode containing a zinc oxide.SOLUTION: A secondary battery comprises a negative electrode containing a zinc oxide, a positive electrode and an alkali electrolytic solution. The secondary battery further comprises a zincic acid ion-supplying source containing zinc oxide or zinc hydroxide between the negative and positive electrodes. The zincic acid ion-supplying source is not electrically connected to any of the negative and positive electrodes. Usually, a separator is disposed between the zincic acid ion-supplying source and the positive electrode. In addition, it is preferred to dispose a nonwoven fabric whose the basis weight is 50 g / m2 or larger, or a porous layer containing insulating particles between the zincic acid ion-supplying source and the negative electrode.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery having a negative electrode containing zinc oxide and having excellent charge-discharge cycle characteristics. [Background technology]

[0002] In recent years, the use of negative electrodes made of metals, alloys, and intermetallic compounds has been considered in constructing secondary batteries with high capacity and high energy density. However, secondary batteries using such negative electrodes have problems such as the generation of dendrites and shape change (aggregation of materials), gas generation, and passivation in the negative electrode, which result in issues with the charge-discharge cycle life.

[0003] Among the above-mentioned negative electrodes, zinc electrodes using zinc or zinc compounds such as zinc alloys and zinc oxide are widely and generally used as alkaline primary batteries using an electrolyte consisting of an alkaline aqueous solution, and the use of such alkaline batteries as secondary batteries is also being considered.

[0004] In alkaline secondary batteries having a zinc electrode, the same problems as above, such as the generation of dendrites, cause a decrease in charge-discharge cycle characteristics, which is an issue. Therefore, attempts have been made to suppress the generation of dendrites by improving the material and structure of the separator (Patent Document 1), using a separator containing a specific metal (Patent Document 2), using a separator having a conductive layer (Patent Document 3), using additives (Patent Documents 4 and 5), and improving the structure of an electrode laminate including a zinc electrode and a positive electrode (Patent Document 6).

[0005] Furthermore, Patent Document 7 proposes a technology in which particulate active material that has a higher potential than the negative electrode is arranged along the surface of a separator to uniformize the current density within the electrode surface and suppress the generation of dendrites due to repeated charging and discharging of a secondary battery. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] U.S. Pat. No. 3,539,396 [Patent Document 2] JP 2006-74541 A [Patent Document 3] JP 2016-146263 A [Patent Document 4] JP 2009-93983 A [Patent Document 5] Special Publication No. 2008-537302 [Patent Document 6] International Publication No. 2017 / 110285 [Patent Document 7] JP 2014-222570 A Summary of the Invention [Problem to be solved by the invention]

[0007] Among the above, in the technology disclosed in Patent Document 5, which uses calcium zincate as an additive to the zinc electrode, calcium ions are supplied from the compound to the electrolyte, thereby suppressing the generation of dendrites. However, by including an insulating material in the zinc electrode, the electrical conductivity of the zinc electrode is impaired, and the charge-discharge cycle characteristics are not sufficiently improved.

[0008] The technology disclosed in Patent Document 7, which uses a material acting as an active material for the negative electrode to suppress the generation of dendrites, can have a certain effect, but since this material has a more noble potential than the negative electrode, it may generate hydrogen gas, which may cause a deterioration in battery characteristics. Also, in the separator described in Patent Document 1, low hydrogen overvoltage materials such as nickel and iron, which are listed as constituent materials of the non-oxidizing film that is a part of the separator, may generate hydrogen and cause a deterioration in battery characteristics.

[0009] For these reasons, in secondary batteries having a zinc electrode, it is necessary to suppress the generation of hydrogen as well as the generation of dendrites that accompanies repeated charge and discharge.

[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a secondary battery having a negative electrode containing zinc oxide and excellent charge-discharge cycle characteristics. [Means for solving the problem]

[0011] The secondary battery of the present invention comprises a negative electrode containing zinc oxide, a positive electrode, and an alkaline electrolyte, and is provided with a zincate ion donor containing zinc oxide or zinc hydroxide, and is characterized in that the zincate ion donor is not conductively connected to either the negative electrode or the positive electrode. Effect of the Invention

[0012] According to the present invention, it is possible to provide a secondary battery having a negative electrode containing zinc oxide and excellent charge / discharge cycle characteristics. [Brief description of the drawings]

[0013] [Figure 1] 2 is a partial cross-sectional view that illustrates a laminate in which the negative electrode, the insulating layer, and the zincate ion donor prepared in Example 1 are laminated. FIG. [Diagram 2] 13 is a diagram for explaining the arrangement of a negative electrode and a zincate ion donor in a secondary battery of Example 6. [Diagram 3] 13 is a diagram for explaining the arrangement of a negative electrode and a zincate ion donor in the secondary battery of Example 7. [Figure 4] 1 is a graph showing the evaluation results of the charge-discharge cycle characteristics at 40° C. of the secondary batteries of Examples 1 to 3 and Comparative Examples 1 and 2. [Diagram 5] 1 is a cross-sectional image obtained by X-ray CT measurement carried out on the secondary battery of Example 1 after 60 charge / discharge cycles. [Figure 6] 1 is a cross-sectional image obtained by X-ray CT measurement carried out on the secondary battery of Comparative Example 1 after 60 charge / discharge cycles. [Figure 7] 1 is a graph showing the evaluation results of the charge-discharge cycle characteristics at 40° C. of the secondary batteries of Examples 5 to 6 and Comparative Example 1. [Figure 8] 1 is a graph showing the evaluation results of the charge-discharge cycle characteristics at 40° C. of the secondary batteries of Example 7 and Comparative Example 1. [Figure 9] 1 is a graph showing the evaluation results of the charge-discharge cycle characteristics at 25° C. of the secondary batteries of Example 1 and Comparative Example 3. [Figure 10] 1 is a graph showing the evaluation results of the charge-discharge cycle characteristics at 40° C. of the secondary batteries of Example 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The secondary battery of the present invention includes a zincate ion donor containing zinc oxide or zinc hydroxide, which can suppress problems such as shape change and passivation of the negative electrode active material, thereby making it possible to suppress a rapid capacity decrease during repeated charging and discharging.

[0015] In addition, since the zincate ion donor is not conductively connected to either the negative electrode or the positive electrode, it is unlikely to be oxidized or reduced during charging and discharging, and problems such as hydrogen generation do not occur.

[0016] In the present invention, the reason why the above-mentioned effects can be ensured is not clear, but it is speculated that it is due to the following mechanism.

[0017] During the charge-discharge cycle, zinc oxide (zinc) which is the active material of the negative electrode repeats a reaction in which it dissolves from the negative electrode into the electrolyte to generate zincate ions, and a reaction in which it precipitates at the negative electrode to generate zinc. In conventional secondary batteries, the movement of the generated zincate ions causes non-uniform precipitation of zinc at the negative electrode, which destroys the uniformity of the zinc distribution in the negative electrode and easily causes the shape change of the negative electrode. In addition, the shape change causes some zinc to become isolated or enlarged and no longer contribute to discharge, which causes part of the negative electrode to become passive and increases the internal resistance, reducing the capacity and becoming one of the factors that shorten the cycle life of the battery.

[0018] On the other hand, in the secondary battery of the present invention, zincate ions ([Zn(OH)4]) are continuously supplied from the zincate ion donor to the alkaline electrolyte. 2- As a result, the deposition of zinc on the negative electrode is made uniform, the morphological change of the negative electrode is suppressed, the passivation of the negative electrode and the increase in internal resistance can be prevented, and the charge-discharge cycle characteristics can be improved.

[0019] Furthermore, even if zinc particles grow large at the negative electrode with repeated charging and discharging of the battery, and zinc dendrites that cannot be discharged grow toward the positive electrode, when the zincate ion donor is provided between the negative electrode (negative electrode mixture layer) and the positive electrode (positive electrode mixture layer), the dendrites are exposed to the potential of zinc oxide or zinc hydroxide the moment they reach the zincate ion donor. Therefore, the tiny metal parts at the tips of the dendrites instantly become zincate ions and dissolve in the electrolyte. Even if metal deposition occurs in the zincate ion donor due to charging the battery, since there is a large amount of zinc oxide around it, the amount of electricity is used to charge the zinc oxide and diffuses, preventing the growth of the dendrites. In this way, in the present invention, by disposing a zincate ion donor between the negative electrode and the positive electrode, in addition to the effect of supplying zincate ions, an effect of preventing short-circuiting due to dendrites during charging and discharging is achieved by a mechanism that does not involve hydrogen generation, such as suppressing the growth of dendrites and diffusing the generated dendrites, and it is presumed that this further improves the charge-discharge cycle characteristics of the secondary battery.

[0020] The negative electrode of the secondary battery of the present invention may have a structure in which a negative electrode mixture layer containing, for example, zinc oxide is formed on a current collector.

[0021] The zinc oxide serving as the active material in the negative electrode preferably has a number average particle size of 0.01 μm or more, more preferably 0.05 μm or more, and preferably 10 μm or less, more preferably 1 μm or less.

[0022] The number average particle size of zinc oxide can be measured, for example, by dispersing zinc oxide in a medium that does not dissolve zinc oxide using a laser scattering particle size distribution meter (e.g., HORIBA's "LA-950V2") (the values ​​described in the examples below are measured using this method).

[0023] The content of zinc oxide in the negative electrode mixture layer is preferably 85 to 99 mass %.

[0024] The negative electrode mixture layer usually contains a binder. Examples of the binder for the negative electrode mixture layer include fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); styrene butadiene rubber (SBR); and the like, with fluororesins being preferred and PTFE being more preferred.

[0025] The content of the binder in the negative electrode mixture layer is preferably 0.1 to 2 mass %. In particular, when a fluororesin is used as the binder, if the content is too high, the water repellency of the negative electrode mixture layer and the composition for forming the negative electrode mixture layer (the negative electrode mixture composition described below) becomes strong, which may result in a decrease in productivity and non-uniform battery reaction.

[0026] The negative electrode mixture layer may contain a conductive assistant, such as acetylene black, ketjen black, carbon blacks such as channel black, furnace black, lamp black, and thermal black, carbon fiber, graphite, and other carbon materials, as well as powders and fibers of metals such as tin, bismuth, silver, and copper.

[0027] The content of the conductive assistant in the negative electrode mixture layer is preferably 0.01 to 5 mass %.

[0028] The negative electrode mixture layer can be formed, for example, by dispersing zinc oxide, and optionally added binders and conductive assistants, in a solvent to prepare a negative electrode mixture composition (such as a paste), and then forming the composition into a sheet (negative electrode mixture sheet) by rolling or the like. This makes it possible to easily form a negative electrode mixture layer with a thickness of, for example, 1 mm or more. By using a negative electrode having a thick negative electrode mixture layer, it becomes possible to obtain a secondary battery with a higher capacity and higher energy density.

[0029] When the negative electrode mixture layer (negative electrode mixture sheet) is used to obtain a negative electrode, the negative electrode mixture layer may be bonded to, for example, a negative electrode current collector.

[0030] In addition, in the case of a negative electrode having a thinner negative electrode mixture layer than the above, for example, a negative electrode mixture composition (such as a slurry) having a lower solid content concentration can be prepared, and this can be applied onto a current collector, dried, and then, if necessary, pressed, to produce the negative electrode.

[0031] Although water is usually used as the solvent for the negative electrode mixture composition, a solvent other than water, such as alcohols (methyl alcohol, ethyl alcohol, isopropyl alcohol, ethylene glycol, etc.), may be appropriately added for the purpose of uniformly dispersing zinc oxide, uniformly dissolving or dispersing the binder, controlling interfacial tension, etc. In addition, an aqueous solution containing an electrolyte salt used as an electrolyte solution for a battery may be used as the solvent for the negative electrode mixture composition.

[0032] The solids concentration of the negative electrode mixture composition (the total content of all components other than the solvent) is preferably 75 to 95 mass %.

[0033] When a particularly thick negative electrode mixture layer is to be formed, it is preferable to add a water-soluble polymer material to the negative electrode mixture composition to increase its viscosity.

[0034] Examples of water-soluble polymeric materials that can be used in the negative electrode mixture composition include CMC (carboxymethylcellulose), PVA (polyvinyl alcohol), PVP (polyvinylpyrrolidone), PAA (polyacrylic acid), polycarboxylate ammonium salts, lecithin, sugars exemplified by glycosides such as saponin and polysaccharides such as xanthan gum, and polyether polyols such as PEO (polyethylene oxide), sucrose polyether polyol, polyoxypropylene sorbitol ether, trimethylolpropane polyether polyol, and pentaerythritol polyether polyol. The negative electrode mixture composition may contain two or more water-soluble polymeric materials.

[0035] Among the water-soluble polymer materials, it is preferable to use at least one of carboxymethyl cellulose and polyether polyol, and it is more preferable to use both carboxymethyl cellulose and polyether polyol.

[0036] The content of the water-soluble polymer material in the negative electrode mixture composition is preferably 0.02% by mass or more, more preferably 0.05% by mass or more, in terms of the amount of all components excluding the solvent (hereinafter referred to as "solid content"), from the viewpoint of favorably thickening the negative electrode mixture composition and making it easier to form a thick negative electrode mixture layer. However, since the water-soluble polymer material acts as a resistance component in the negative electrode mixture layer after formation, if the amount of the water-soluble polymer material in the negative electrode mixture composition is too large, there is a risk of impairing the characteristics (capacity, etc.) of the secondary battery. Therefore, the content of the water-soluble polymer material in the negative electrode mixture composition is preferably 0.2% by mass or less, more preferably 0.15% by mass or less, in terms of the amount of the solid content.

[0037] The method for preparing the negative electrode mixture composition is not particularly limited, and any method may be adopted as long as it can uniformly disperse zinc oxide, binder, and conductive assistant in the mixture composition, and, in the case of using a water-soluble polymer material, can uniformly dissolve the water-soluble polymer material in the mixture composition.

[0038] The thickness of the negative electrode mixture layer can be 0.1 mm or more, but from the viewpoint of increasing the energy density of the secondary battery, it is preferably 1 mm or more, more preferably 1.5 mm or more, and the upper limit of the thickness of the negative electrode mixture layer is preferably, for example, 10 mm.

[0039] Examples of the negative electrode current collector include a mesh, foil, expanded metal, punched metal, foam metal, etc. of a metal such as nickel, copper, or stainless steel; a carbon sheet or mesh; etc., and it is preferable that the current collector is coated, for example, by plating, with a material having a high hydrogen overvoltage, such as tin, lead, or indium. The thickness of the negative electrode current collector is preferably 5 to 300 μm.

[0040] Furthermore, in the secondary battery of the present invention, as described below, a sheet-like outer casing can be applied, and a carbon paste can be applied to the surface of this sheet-like outer casing that is intended to become the inner surface (the surface that comes into contact with the sheet that will become the negative electrode mixture layer) to serve as a current collector for the negative electrode, or a metal layer (described below) that constitutes the sheet-like outer casing can be used as a current collector for the negative electrode.

[0041] The negative electrode can be provided with an external terminal in a conventional manner for electrically connecting the secondary battery to a device to which it is applied.

[0042] The capacity per area of ​​the negative electrode mixture layer is 150mAh / cm 2 It is preferable that the capacity is 300 mAh / cm or more. 2 By using a negative electrode having such a capacity, a secondary battery having a high energy density can be obtained.

[0043] In the case of a secondary battery using a negative electrode having a thick negative electrode mixture layer, for example, 1 mm or more, or a negative electrode having a large capacity per area as described above, dendrites are more likely to occur than in a secondary battery using a negative electrode having a thin negative electrode mixture layer or a negative electrode having a small capacity per area, probably because the current value per area is larger even at the same discharge rate. However, in the secondary battery of the present invention, when a zincate ion donor is disposed between the negative electrode (negative electrode mixture layer) and the positive electrode (positive electrode mixture layer), the occurrence of problems due to dendrites can be effectively suppressed by the action of the zincate ion donor. Therefore, in the secondary battery of the present invention, when a high capacity is achieved by using a negative electrode having a thick negative electrode mixture layer, for example, 1 mm or more, or a negative electrode having a large capacity per area as described above, the effect of disposing the zincate ion donor between the negative electrode and the positive electrode is particularly remarkable.

[0044] The capacity per unit area of ​​the negative electrode mixture layer can be controlled to the above value by adjusting the thickness and packing density of the negative electrode mixture layer (and the associated amount of negative electrode active material per unit area of ​​the negative electrode mixture layer). It is known that each type of negative electrode active material has a unique capacity, and the values ​​are also published, so this value is used when calculating the capacity per unit area of ​​the negative electrode mixture layer.

[0045] The packing density of the negative electrode mixture layer is 1.8 to 2.8 g / cm 3 is good, 2.1~2.4g / cm 3 If the packing density is too high, the porosity of the negative electrode mixture layer becomes too low, making it difficult for the electrolyte to permeate into the negative electrode mixture layer, which may result in a deterioration in the battery characteristics.

[0046] The zincate ion donor is not particularly limited in its composition as long as it contains zinc oxide or zinc hydroxide, and may have the same composition (component composition and charge density) as the negative electrode mixture layer of the negative electrode. However, it is preferable that the zincate ion donor does not contain a conductive assistant.

[0047] In addition, the shape of the zincate ion donor is not particularly limited as long as it can continuously supply zincate ions to the alkaline electrolyte, but when it is placed between the negative electrode and the positive electrode, it is preferable to form it in a layer (plate) shape.

[0048] The thickness of the zincate ion donor in the case of forming it in a layer (plate) shape is preferably 0.1 mm or more, more preferably 0.25 mm or more, from the viewpoint of suppressing the occurrence of short circuit caused by dendrites and improving the charge-discharge cycle characteristics of the secondary battery. However, even if the zincate ion donor is made thick, not only the effect is saturated, but also if the donor is too thick, there is a risk of the battery characteristics (capacity, etc.) decreasing, so that the thickness is preferably 2.4 mm or less, more preferably 1.2 mm or less.

[0049] When a zincate ion donor is disposed between a negative electrode and a positive electrode, from the viewpoint of better ensuring the effect of suppressing problems caused by dendrites, the area of ​​the zincate ion donor in a planar view is preferably equal to or larger than the area of ​​the negative electrode mixture layer in a planar view, and more preferably larger than the area of ​​the negative electrode mixture layer in a planar view.

[0050] In order to better ensure the effect of suppressing the problems caused by dendrites, the total content per unit area of ​​zinc oxide and zinc hydroxide in the zincate ion donor is preferably 10% by mass or more, more preferably 25% by mass or more, of the content per unit area of ​​zinc oxide in the negative electrode. In order to suppress the capacity decrease of the battery as much as possible by suppressing the volume ratio of the zincate ion donor that is not involved in the charge / discharge reaction of the battery in the battery, the total content per unit area of ​​zinc oxide and zinc hydroxide in the zincate ion donor is preferably 300% by mass or less, more preferably 250% by mass or less, of the content per unit area of ​​zinc oxide in the negative electrode.

[0051] Note that the zinc oxide in the negative electrode changes to metallic zinc upon charging, and the content of zinc oxide per unit area in the negative electrode can be determined by converting the zinc in metallic state into zinc oxide.

[0052] In order to prevent the zincate ion donor from being electrically connected to the positive electrode and the negative electrode, it is preferable to interpose an insulating layer between the zincate ion donor and the negative electrode to prevent them from contacting each other.

[0053] The insulating layer interposed between the zincate ion donor and the negative electrode may be any layer capable of transporting the electrolyte necessary for the electrochemical reaction in the negative electrode mixture layer and insulating the zincate ion donor. For example, it may be a general insulator, i.e., a layer having a high resistance of 1,000,000 Ωm or more, a material that is stable in the battery, and a form (porous layer) having voids through which the electrolyte can permeate. More specifically, the insulating layer may be a nonwoven fabric or microporous membrane made of a resin capable of insulating the zincate ion donor; a sheet-like material such as a woven fabric or filter made of an inorganic material; a porous layer containing insulating particles such as resin or inorganic particles, fibers, or composites thereof; etc. Among them, a nonwoven fabric made of polyolefin such as polyethylene (PE) or polypropylene (PP); or a porous layer containing inorganic particles such as oxides (aluminum oxide, titanium oxide, zirconium oxide, silicon oxide, etc.) or nitrides (titanium nitride, silicon nitride, etc.); is more preferable.

[0054] The porous layer containing insulating particles can be produced, for example, by dispersing the insulating particles and components that are added as necessary, such as a binder, a thickener, and a dispersant, in a solvent to form a mixture composition, and then forming the composition into a sheet by rolling or the like.

[0055] In addition, the solid content concentration of the mixture composition is adjusted to prepare a coating composition, which is then applied to an insulating substrate such as a nonwoven fabric, and the coating film is held by the substrate, thereby improving the shape retention of the porous layer.

[0056] Furthermore, a porous layer may be formed on the surface of the negative electrode by applying a coating composition onto the negative electrode.

[0057] When a nonwoven fabric is used as the insulating layer, the basis weight of the nonwoven fabric is set to 40 g / m2 or less in order to effectively isolate the negative electrode and the zincate ion donor and to more effectively prevent conductive connection between them. 2 It is preferable that the thickness is 50 g / m or more. 2 However, since the insulating layer acts as a resistance layer in the secondary battery, if the basis weight is too large, there is a risk of impairing the battery characteristics of the secondary battery. Therefore, from the viewpoint of improving the battery characteristics of the secondary battery, the basis weight of the nonwoven fabric that becomes the insulating layer is 500 g / m or more. 2 It is preferable that the thickness is less than 300 g / m 2 It is more preferable that:

[0058] When a porous layer is used as an insulating layer, the porosity of the porous layer is preferably 70% or less in order to effectively isolate the negative electrode and the zincate ion donor and to more effectively prevent conductive connection between them, while the porosity of the porous layer is preferably 30% or more in order to improve the battery characteristics without inhibiting ion conductivity.

[0059] Furthermore, a separator may be interposed between the zincate ion donor and the positive electrode to prevent them from contacting each other (details of the separator will be described later).

[0060] The secondary battery of the present invention may have the above-mentioned negative electrode and zincate ion donor, and the configurations of the positive electrode, separator, alkaline electrolyte, etc. are not particularly limited, and general-purpose positive electrodes, separators, alkaline electrolytes, etc. used in alkaline secondary batteries and air secondary batteries can be used.

[0061] When the secondary battery is an alkaline secondary battery, the positive electrode may have a structure in which a positive electrode mixture layer containing a positive electrode active material, a conductive assistant, and a binder is provided on one or both sides of a current collector.

[0062] When the secondary battery is an alkaline secondary battery, examples of usable positive electrode active materials include silver oxide (silver(I) oxide, silver(II) oxide, etc.); manganese oxides such as manganese dioxide; nickel oxyhydroxide; and composite oxides of silver and cobalt, nickel, or bismuth.

[0063] Examples of the conductive assistant for the positive electrode mixture layer that can be used include carbon materials such as acetylene black; ketjen black; carbon blacks such as channel black, furnace black, lamp black, and thermal black; and carbon fibers; as well as conductive fibers such as metal fibers; carbon fluoride; metal particles such as copper and nickel; and organic conductive materials such as polyphenylene derivatives.

[0064] Examples of the binder for the positive electrode mixture layer include fluororesins (PVDF, PTFE, etc.), SBR, CMC, and polyvinylpyrrolidone (PVP).

[0065] The positive electrode mixture layer preferably contains 80 to 98% by mass of positive electrode active material, 1.5 to 10% by mass of conductive additive, and 0.5 to 10% by mass of binder. The thickness of the positive electrode mixture layer (thickness per surface of the current collector) is preferably 1 to 20 mm.

[0066] A positive electrode having a positive electrode mixture layer can be manufactured, for example, by dispersing a positive electrode active material, a conductive assistant, a binder, and the like in water or an organic solvent such as N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture-containing composition (slurry, paste, etc.) (the binder may be dissolved in the solvent), applying this onto a current collector, drying it, and, if necessary, subjecting it to a pressing process such as calendaring.

[0067] When the secondary battery is an air secondary battery, the positive electrode may have a catalyst layer, for example, a structure in which a catalyst layer and a current collector are laminated.

[0068] The catalyst layer may contain a catalyst, a binder, and the like.

[0069] Examples of the catalyst for the catalyst layer include silver, platinum group metals or alloys thereof, transition metals, platinum / metal oxides such as Pt / IrO2, La 1-x Ca x Examples of known materials include perovskite oxides such as CoO3, brownmillerite transition metal oxides such as Ca2Fe2O5 and Ca2FeCoO5, carbides such as WC, nitrides such as Mn4N, manganese oxides such as manganese dioxide, and carbon (graphite, carbon black (acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, etc.), charcoal, activated carbon, etc.), and one or more of these may be used.

[0070] The catalyst layer preferably contains 1% by mass or less of heavy metals, excluding the components of the electrolyte. In the case of a positive electrode having a catalyst layer with such a low content of heavy metals, the battery can be disposed of without any special treatment, resulting in a battery with low environmental impact.

[0071] The content of heavy metals in the catalyst layer as referred to in this specification can be measured by fluorescent X-ray analysis. For example, it can be measured using Rigaku's "ZSX100e" under the conditions of excitation source: Rh50kV, and analysis area: φ10mm.

[0072] Therefore, it is recommended that the catalyst for the catalyst layer not contain heavy metals, and it is more preferable to use the various carbons mentioned above.

[0073] Examples of the binder for the catalyst layer include fluororesin binders such as PVDF, PTFE, vinylidene fluoride copolymers and tetrafluoroethylene copolymers [vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), vinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), vinylidene fluoride-tetrafluoroethylene copolymer (PVDF-TFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (PVDF-HFP-TFE), etc.]. Among these, tetrafluoroethylene polymers (PTFE) or copolymers are preferred, and PTFE is more preferred.

[0074] In the case of a positive electrode having a catalyst layer, for example, the catalyst, binder, etc. can be mixed with water, rolled with a roll, and attached to a current collector. Alternatively, the catalyst and the binder used as needed can be dispersed in water or an organic solvent to prepare a catalyst layer forming composition (slurry, paste, etc.), which is applied to the surface of a current collector, dried, and then, if necessary, subjected to a pressing process such as a calendaring process.

[0075] For the current collector for a positive electrode having a positive electrode mixture layer or a positive electrode having a catalyst layer, for example, a mesh, foil, expanded metal, or punched metal of a metal such as titanium, nickel, stainless steel, or copper; a carbon mesh or sheet; or the like can be used.

[0076] Furthermore, in the secondary battery of the present invention, a sheet-like outer casing can be applied as described below, and a carbon paste can be applied to the surface of this sheet-like outer casing that is intended to become the inner surface to serve as a positive electrode current collector, or a metal layer (described below) that constitutes the sheet-like outer casing can be used as a positive electrode current collector.

[0077] The positive electrode can be provided with an external terminal in a conventional manner for electrically connecting the secondary battery to a device to which the secondary battery is applied.

[0078] Examples of separators for secondary batteries include separators that are generally used in various batteries, such as resin porous membranes (microporous membranes, nonwoven fabrics, etc.) and semipermeable membranes such as cellophane films. In particular, when the secondary battery is an air secondary battery, it is preferable to use an anion conductive membrane or a semipermeable membrane as the separator from the viewpoint of preventing short circuits and improving load characteristics.

[0079] Examples of the resin that constitutes the separator made of a resin porous film include polyolefins such as PE, PP, and ethylene-propylene copolymers.

[0080] In the case of a resin separator, the porosity is preferably 30 to 80%, and the thickness is preferably 10 to 100 μm, but multiple sheets may be stacked.

[0081] Furthermore, when a semipermeable membrane such as a cellophane film is used as the separator, the separator may be composed of only the semipermeable membrane. However, since the semipermeable membrane has low strength, problems such as breakage during battery assembly are likely to occur. Therefore, it is also recommended to compose the separator with a laminate in which a semipermeable membrane and a graft film composed of a polymer in which (meth)acrylic acid or its derivative is graft-polymerized onto a polyolefin trunk polymer (polyethylene, polypropylene, etc.) are laminated. Note that the above-mentioned "(meth)acrylic acid" is a collective expression for acrylic acid and methacrylic acid.

[0082] In the case of a separator formed only of a cellophane film, the thickness is, for example, preferably 15 μm or more and preferably 40 μm or less, and more preferably 30 μm or less.

[0083] Furthermore, in the case of a separator composed of a laminate of a graft film and a cellophane film, the total thickness of the graft film and the cellophane film is, for example, preferably 30 μm or more, more preferably 40 μm or more, and preferably 70 μm or less, more preferably 60 μm or less.

[0084] Furthermore, in the case of a separator formed of a laminate of a graft film and a cellophane film, the thickness of the graft film is, for example, preferably 15 μm or more, more preferably 25 μm or more, and preferably 30 μm or less.

[0085] Examples of laminates of a graft film and a cellophane film for forming a separator include those commercially available from Yuasa Membrane Systems Co., Ltd. under the names "YG9132", "YG9122", and "YG2152".

[0086] Alternatively, the separator may be formed by combining a cellophane film, or a combination of a cellophane film and a graft film with a liquid-absorbing layer (electrolyte solution retaining layer) such as vinylon-rayon mixed paper. The thickness of such a liquid-absorbing layer is preferably 20 to 500 μm.

[0087] For the alkaline electrolyte of the secondary battery, an alkaline aqueous solution having a high pH (for example, pH 14 or higher) that is a strong alkali is preferably used from the viewpoint of ion conductivity, but an electrolyte having a lower pH, for example, a pH of about 12, can also be used.

[0088] Examples of the electrolyte salt in the aqueous solution include hydroxides of alkali metals and alkaline earth metals (sodium hydroxide, potassium hydroxide, lithium hydroxide, magnesium hydroxide, calcium hydroxide, etc.), and the aqueous solution may contain one or more of these electrolyte salts.

[0089] The concentration of the electrolyte salt in the aqueous solution may be any concentration that allows the electrical conductivity of the aqueous solution to be adjusted to about 80 to 700 mS / cm, and is usually 5 to 50 mass %.

[0090] In addition, it is preferable that an indium compound is dissolved in the aqueous solution. When an indium compound is dissolved in the aqueous solution, generation of hydrogen gas in the battery can be effectively suppressed.

[0091] Examples of the indium compound to be dissolved in the aqueous solution include indium hydroxide, indium oxide, indium sulfate, indium sulfide, indium nitrate, indium bromide, and indium chloride.

[0092] The concentration of the indium compound in the aqueous solution is preferably 0.005% or more, more preferably 0.01% or more, and particularly preferably 0.05% or more, and is preferably 1% or less, and more preferably 0.5% or less, based on mass. It is particularly preferable that the content be 0.1% or less.

[0093] In addition to the above-mentioned components, various known additives may be added to the aqueous solution, if necessary.

[0094] The shape of the secondary battery is not particularly limited, and the battery may be in any shape, such as a flat shape (including a coin shape and a button shape) having a battery case in which the outer can and the sealing plate are crimped and sealed via a gasket, or the outer can and the sealing plate are sealed by welding together; a sheet shape having a sheet-like outer body made of a resin film; or a cylindrical shape (cylindrical shape, square shape (square cylindrical shape)) having a battery case in which the outer can and the sealing plate are crimped and sealed via a gasket, or the outer can and the sealing plate are sealed by welding together.

[0095] Examples of the resin film constituting the sheet-like exterior body include nylon film (such as nylon 66 film), polyester film (such as polyethylene terephthalate (PET) film), etc. The thickness of the resin film is preferably 20 to 100 μm.

[0096] In addition, the sheet-like outer packaging is generally sealed by heat-sealing the end of the upper resin film and the end of the lower resin film of the sheet-like outer packaging, but in order to make this heat-sealing easier, a heat-sealing resin layer may be laminated on the resin film exemplified above and used for the sheet-like outer packaging. Examples of heat-sealing resins constituting the heat-sealing resin layer include modified polyolefin films (such as modified polyolefin ionomer films), polypropylene and copolymers thereof. The thickness of the heat-sealing resin layer is preferably 20 to 100 μm.

[0097] A metal layer may be laminated on the resin film. The metal layer may be made of an aluminum film (aluminum foil, including aluminum alloy foil), a stainless steel film (stainless steel foil), etc. The thickness of the metal layer is preferably 10 to 150 μm.

[0098] The resin film constituting the sheet-like exterior body may be a film having a configuration in which the above-mentioned heat-sealable resin layer and the above-mentioned metal layer are laminated together.

[0099] The shape of the sheet-like exterior body may be polygonal (triangle, quadrangle, pentagon, hexagon, heptagon, octagon) in plan view, or may be circular or elliptical in plan view. In the case of a sheet-like exterior body that is polygonal in plan view, the positive electrode external terminal and the negative electrode external terminal may be drawn to the outside from the same side, or each may be drawn to the outside from a different side.

[0100] Furthermore, when using an exterior body that performs crimping sealing, the material of the gasket interposed between the exterior can and the sealing plate can be polypropylene, nylon, etc., or fluororesin such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), etc. Also, a glass hermetic seal can be used for sealing.

[0101] When the secondary battery is an air secondary battery, an air hole is formed in the exterior body to take in air to the positive electrode (air electrode). There is no particular limit to the number of air holes, and it is sufficient to select a number that can take in enough air to allow the air battery to discharge satisfactorily. There is also no particular limit to the shape of the air hole, and it may be circular in plan view, or may be elliptical or polygonal (triangle, square, etc.).

[0102] In addition, when the secondary battery is an air secondary battery, it is preferable to dispose a water-repellent film between the positive electrode (air electrode) and the exterior body in order to prevent moisture from entering the inside of the battery through the air holes. The water-repellent film is a film that is water-repellent but air-permeable, and specifically, a film made of a resin such as fluororesin such as PTFE; polyolefin such as PP or PE; etc., can be used. The thickness of the water-repellent film is preferably 50 to 250 μm.

[0103] In addition, when the secondary battery is an air secondary battery, an air diffusion membrane for supplying air taken into the exterior body to the positive electrode may be disposed between the exterior body and the water-repellent film. The air diffusion membrane may be a nonwoven fabric made of a resin such as cellulose, polyvinyl alcohol, PP, or nylon. The thickness of the air diffusion membrane is preferably 100 to 250 μm.

[0104] The secondary battery of the present invention can be used in the same applications as general-purpose alkaline secondary batteries and air secondary batteries. EXAMPLES

[0105] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0106] Example 1 <Preparation of Laminate of Negative Electrode, Insulating Layer, and Zinc Ion Donor> A negative electrode mixture composition with a solid content of 78.2% by mass was prepared by mixing 93.5% by mass of zinc oxide (number average particle size 0.6 μm), 1.5% by mass of PTFE, and 5% by mass of acetylene black with water. The negative electrode mixture composition was mixed in a self-rotating mixer at 2000 rpm for 5 minutes to obtain a lump mixture, which was stretched through a gap of 0.6 mm in thickness multiple times in a roll press machine to form a lump, and then the gap of the roll press was adjusted to form a sheet of 0.6 mm in thickness, which was then cut to obtain a rectangular negative electrode mixture sheet of 20 mm × 20 mm.

[0107] Two sheets of the above negative electrode mixture were prepared and cut into an insulating layer of 21 mm x 21 mm. Thickness: 125 μm, basis weight: 54 g / m 2 The polypropylene nonwoven fabric was sandwiched at the center, and a copper wire net having a mesh of 100 mesh cut to 20 mm x 23 mm was placed on one side as a current collector, and molded with a gap of 1.2 mm using a roll press. Next, a copper lead having a thickness of 100 μm and a width of 3 mm was welded to the exposed part of the current collector protruding from the two negative electrode mixture sheets to form a current extraction part. Furthermore, a polypropylene sheet was heat-welded to the exposed part of the wire net to obtain a laminate in which three layers, a layer (A) made of a negative electrode mixture sheet, a layer (B) made of an insulating layer and a negative electrode mixture sheet, were laminated on one side of the current collector. In the laminate, the total thickness of the layer (A) made of a negative electrode mixture sheet, the insulating layer and the layer (B) made of a negative electrode mixture sheet was 1.3 mm.

[0108] FIG. 1 shows a schematic partial cross-sectional view of the laminate. In the laminate 1, the layer (A) 21 made of the negative electrode mixture sheet on the current collector 22 side is electrically connected by contacting with the current collector 22 to become a negative electrode mixture layer (a negative electrode mixture layer containing a negative electrode active material), and the layer (A) (negative electrode mixture layer) 21 made of the negative electrode mixture sheet and the current collector 22 constitute the negative electrode 2. In addition, the layer (B) 3 made of the negative electrode mixture sheet laminated with the layer (A) 21 made of the negative electrode mixture sheet on the current collector side via the insulating layer 4 is not electrically connected to the negative electrode 2 [the layer (A) 21 made of the negative electrode mixture sheet and the current collector 22] and is a zincate ion donor. The content of zinc oxide per unit area in the zincate ion donor is designed to be the same value (100 mass%) as the content of zinc oxide per unit area in the negative electrode.

[0109] <Preparation of positive electrode> Nickel hydroxide: 89.8 mass%, CMC: 0.2 mass%, cobalt monoxide: 5 mass%, and tricobalt tetroxide: 5 mass% were mixed with water to prepare a positive electrode mixture composition with a solid content concentration of 75 mass%. This positive electrode mixture composition was mixed in a self-rotating mixer at 2000 rpm for 5 minutes, and then PTFE was added at a ratio of 0.9 mass parts per 100 mass parts of nickel hydroxide, and mixed at 2000 rpm for 30 seconds. The obtained mixture was filled into a 2 mm thick foamed nickel so that a part was left uncoated, and the mixture was dried at 80 ° C for 1 hour, and then the thickness was reduced to 1 mm by roll press. This was cut to form an electrode having a 25 mm × 25 mm square positive electrode mixture layer forming part and a 3 mm wide current collector (foamed nickel) exposed part. Two of these electrodes were stacked and integrated by roll pressing, and a nickel lead having a thickness of 100 μm and a width of 3 mm was welded to the exposed part of the current collector to form a current extraction part, thereby obtaining a positive electrode having a thickness of 2 mm.

[0110] <Preparation of electrolyte> An excess of commercially available zinc oxide was dissolved in a commercially available 8M aqueous potassium hydroxide solution, the solution was stirred at room temperature for more than 12 hours, and the remaining zinc oxide was filtered to prepare an alkaline electrolyte containing zinc oxide dissolved at a saturated concentration.

[0111] <Assembling alkaline secondary batteries> An alkaline secondary battery (model cell) was assembled using the prepared negative electrode, the above positive electrode, and the above electrolyte.

[0112] A separator was used in combination with two 30 μm graft films and a 120 μm polypropylene nonwoven fabric, and the laminate of the negative electrode, insulating layer, and dendrite suppression layer and the positive electrode were stacked with the separator in between to form an electrode body. In the electrode body, the laminate was arranged so that the zincate ion donor was in contact with the separator. Two polypropylene sheets molded to 35 mm x 60 mm so that the electrode body would fit in were stacked, and three sides were welded into a bag to form an exterior body. After inserting the electrode body into this, the electrode body was sandwiched from both sides with 50 mm x 50 mm x 8 mm acrylic plates and screwed at the four corners. Then, 3.5 ml of the electrolyte was injected into the exterior body to vacuum impregnate it, and the remaining side of the exterior body was sealed to complete the model cell.

[0113] Example 2 An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that the thickness of the layer (B) made of the negative electrode mixture sheet was set to 1.2 mm, and the content of zinc oxide per unit area in the zincate ion donor was set to twice (200 mass%) the content of zinc oxide per unit area in the negative electrode.

[0114] Example 3 <Creating the insulating layer> 83.7 parts by mass of aluminum oxide with a number average particle size of secondary aggregates of 50 μm, 15.5 parts by mass of PTFE, 0.4 parts by mass of carboxymethylcellulose, and 0.4 parts by mass of ammonium polycarboxylate are mixed with water to prepare a mixture composition with a solid content concentration of 61% by mass. This composition is mixed in a planetary mixer at 2000 rpm for 5 minutes, and then formed into a sheet with a thickness of 1.0 mm using a roll press machine, which is cut to obtain a rectangular porous sheet containing aluminum oxide with a size of 20 mm x 20 mm.

[0115] An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that the porous sheet was used as the insulating layer instead of the polypropylene nonwoven fabric.

[0116] Example 4 An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that the thickness of the layer (B) made of the negative electrode mixture sheet was set to 0.15 mm, and the content of zinc oxide per unit area in the zincate ion donor was set to ¼ times (25 mass%) the content of zinc oxide per unit area in the negative electrode.

[0117] Example 5 Two negative electrode mixture sheets were prepared by cutting the negative electrode mixture sheets to a size of 20 mm x 20 mm and a thickness of 0.6 mm in the same manner as in Example 1. Next, a negative electrode mixture sheet having a thickness of 125 μm and a basis weight of 54 g / m 2 Two pieces of polypropylene nonwoven fabric were formed into a bag shape, one of the negative electrode mixture sheets was placed inside the bag, and the opening was heat-sealed to prepare a zincate ion donor enclosed in an insulating layer made of polypropylene nonwoven fabric.

[0118] Furthermore, the remaining negative electrode mixture sheet was pressed onto one side of a copper wire mesh (20 mm × 23 mm) having 100 meshes, the same as that used in Example 1, which served as a current collector, using a roll press, and a copper lead having a thickness of 100 μm and a width of 3 mm was welded to the exposed portion at the end of the current collector to form a current extraction portion, thereby producing a negative electrode in which the negative electrode mixture layer and the current collector were integrated.

[0119] An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that the negative electrode, the zincate ion donor coated with an insulating layer, the same separator as in Example 1, and the positive electrode were laminated in this order to form an electrode body.

[0120] Example 6 A negative electrode mixture sheet cut to 20 mm x 20 mm with a thickness of 1.2 mm was prepared in the same manner as in Example 1, except that the gap of the roll press was changed to 1.2 mm. Next, the negative electrode mixture sheet was cut in half to make two sheets with a size of 10 mm x 20 mm, and one of the sheets was pressed by a roll press onto one side of a copper wire mesh (20 mm x 23 mm) having a mesh size of 100 mesh, the same as that used in Example 1, which served as a current collector. As shown in FIG. 2, the negative electrode mixture sheet (21) was disposed so that exposed portions of the current collector 22 having a width of 3 mm and a width of 10 mm were formed on both sides of the 20 mm side, and a copper lead having a thickness of 100 μm and a width of 3 mm was welded to the exposed portion of the current collector 22 having a width of 3 mm [the upper side of the negative electrode mixture sheet (21) in FIG. 2] to form a current extraction portion 23. Thus, a negative electrode having the same capacity as in Example 5 was produced in which the negative electrode mixture layer 21 and the current collector 22 having dimensions of 10 mm×20 mm were integrated.

[0121] Thickness 125μm, basis weight 54g / m 2 The two polypropylene nonwoven fabrics were formed into a bag shape, the other negative electrode mixture sheet was placed inside the bag, and the opening was heat-sealed to prepare a zincate ion donor enclosed in an insulating layer made of polypropylene nonwoven fabric.

[0122] An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that a zincate ion donor 3 covered with an insulating layer was laminated on the exposed portion of the negative electrode current collector 22 having a width of 10 mm (the lower side of the negative electrode mixture sheet (21) in FIG. 2 ) so as to be aligned with the negative electrode mixture layer 21, and further, a separator and a positive electrode the same as those used in Example 1 were laminated thereon in this order to form an electrode body.

[0123] Example 7 As shown in FIG. 3, a negative electrode was prepared so that a 10 mm×20 mm negative electrode mixture layer 21 and a 10 mm-wide exposed portion of the current collector 22 (on the right side of the negative electrode mixture sheet (21) in FIG. 3) were formed side by side in the length direction of an exposed portion of the current collector 22 with a width of 3 mm (the upper side of the negative electrode mixture sheet (21) in FIG. 3) and a zincate ion donor 3 was disposed in the exposed portion of the current collector 22 with a width of 10 mm. An alkaline secondary battery (model cell) was assembled in the same manner as in Example 6.

[0124] Comparative Example 1 A negative electrode mixture sheet was prepared in the same manner as in Example 1, except that the thickness was changed to 1.2 mm, and this negative electrode mixture sheet was placed on one side of a copper wire netting having a mesh of 100 meshes cut to 20 mm x 23 mm, and molded by a roll press machine, to obtain a negative electrode (a negative electrode without a zincate ion donor and an insulating layer) having a negative electrode mixture layer with a thickness of 1.3 mm on one side of a current collector in the same manner as in Example 1. Then, an alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that this negative electrode was used instead of the laminate of the negative electrode, the insulating layer, and the zincate ion donor.

[0125] Comparative Example 2 A laminate (a laminate of a negative electrode and a zincate ion donor) was prepared in the same manner as in Example 1, except that no insulating layer was placed between the two negative electrode mixture sheets. An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that this laminate was used.

[0126] Comparative Example 3 The positive electrode mixture layer forming portion of the electrode having a thickness of 1 mm used in producing the positive electrode in Example 1 was cut to produce a square positive electrode mixture sheet of 20 mm x 20 mm composed of the positive electrode mixture composition and the current collector.

[0127] An alkaline secondary battery (model cell) was assembled in the same manner as in Example 1, except that the positive electrode mixture sheet was used instead of the layer (B) made of the negative electrode mixture sheet.

[0128] The charge / discharge cycle characteristics of the secondary batteries of Examples 1 to 3, Examples 5 and 6, and Comparative Examples 1 and 2 were evaluated in an atmosphere of 40° C. by the following method.

[0129] For each of the secondary batteries of Examples 1 to 3, Examples 5 to 6, and Comparative Examples 1 to 2, at a current value of 64 mA, (1) The charging capacity reaches 320mAh. (2) The battery voltage reaches 2.2V during charging. (3) The battery voltage during charging drops by 50 mV from the maximum value (-ΔV = 50 mV). Charge the battery until either of the following conditions is met, then charge it at a current of 64mA. (4) The battery voltage reaches 1.0 V during discharging. (5) The discharged electricity amount reaches 320mAh. The charge-discharge cycle was repeated until any of the following conditions was met, and the discharge capacity was measured at the first cycle (initial time) and every 10 cycles thereafter to evaluate the charge-discharge cycle characteristics.

[0130] The measured discharge capacity of each of the batteries of Examples 1 to 3 and Comparative Examples 1 and 2 is shown in FIG. 4, expressed as a relative value when the initial discharge capacity of each battery is set to 100.

[0131] In addition, after 60 cycles of charge and discharge were repeated for the batteries of Example 1 and Comparative Example 1, non-destructive cross-section observation of the cells was performed using an X-ray CT scanner. The cross-sectional images obtained at that time are shown in Figs. 5 and 6.

[0132] X-ray CT observation was performed using a Bruker "skyscan1173 (product name)" under conditions of 130 kV and 61 μA. The obtained image data was then reconstructed using the accompanying application, and cross-sectional data was extracted and displayed in grayscale. Materials with high absorption coefficients and high density, such as the copper current collector, the grown zinc metal, and the nickel foam in the positive electrode, are displayed in bright white, while oxides such as zinc oxide and nickel hydroxide have low absorption coefficients and density and are displayed in dark gray. Materials with extremely low absorption coefficients and density, such as the separator, electrolyte, and air, are displayed in black.

[0133] 5, in the secondary battery of Example 1, even after 60 cycles of charge and discharge, the zincate ion donor 3 suppressed the morphological change of the negative electrode, and prevented the growth of the metallic zinc dendrites 100 from the negative electrode mixture layer beyond a certain level, thereby preventing the dendrites from penetrating the positive electrode 5. Therefore, the negative electrode was less likely to be passivated or an internal short circuit occurred, and as shown in FIG. 4, the secondary battery of Example 1 was able to sufficiently maintain a large capacity even after 80 cycles of charge and discharge.

[0134] In addition, the secondary battery of Example 2, in which the content of zinc oxide per unit area in the zincate ion donor is made larger than that of Example 1, and the secondary battery of Example 3, in which a porous sheet containing aluminum oxide is used as an insulating layer, were able to further improve the charge-discharge cycle characteristics compared to the secondary battery of Example 1, as shown in FIG. 4.

[0135] In contrast, in the battery of Comparative Example 1 not having a zincate ion donor, the capacity suddenly decreased after about 40 charge / discharge cycles as shown in Fig. 4. As shown in Fig. 6, in the battery of Comparative Example 1, the morphological change of the negative electrode became significant after 60 charge / discharge cycles, and further, the dendrites of metallic zinc that had grown from the negative electrode mixture layer reached the positive electrode, which is considered to have caused the above-mentioned capacity decrease due to the passivation of the negative electrode and an internal short circuit.

[0136] In the battery of Comparative Example 2, since the two negative electrode mixture sheets were in contact with each other without an insulating layer being placed between them, the negative electrode mixture sheet placed on the positive electrode side was also charged and functioned as a negative electrode, and as in Comparative Example 1, passivation of the negative electrode and an internal short circuit occurred, which is thought to have resulted in a rapid decrease in capacity after about 40 charge-discharge cycles.

[0137] FIG. 7 shows the results of measuring the discharge capacity of each of the batteries of Examples 5 and 6 and Comparative Example 1, expressed as a relative value when the initial discharge capacity of each battery was set to 100.

[0138] Furthermore, for the batteries of Example 7 and Comparative Example 1, the charge / discharge cycle was repeated under the same conditions as above except that the current value was changed to 128 mA, and the discharge capacity for each cycle was measured to evaluate the charge / discharge cycle characteristics. The results of the discharge capacity of each battery expressed as a relative value when the initial discharge capacity of each battery was set to 100 are shown in FIG.

[0139] In the batteries of Examples 6 and 7, no zincate ion donor was disposed between the negative electrode mixture layer and the positive electrode mixture layer. However, zincate ions were continuously supplied from the zincate ion donor to the alkaline electrolyte, and thus the charge-discharge cycle characteristics were improved compared to the secondary battery of Comparative Example 1, similar to the battery of Example 5 in which the zincate ion donor was disposed between the negative electrode mixture layer and the positive electrode mixture layer.

[0140] Moreover, for the secondary batteries of Example 1 and Comparative Example 3, charge / discharge cycles were repeated under the same conditions as above in an atmosphere of 25° C., and the charge / discharge cycle characteristics were evaluated.

[0141] The discharge capacity of each battery was measured for each cycle, and the results are shown in FIG. 9, expressed as a relative value with the initial discharge capacity taken as 100.

[0142] The secondary battery of Example 1 in which the zincate ion donor was formed using zinc oxide was able to perform stable charging and discharging without generating hydrogen from the zincate ion donor.

[0143] On the other hand, in the secondary battery of Comparative Example 3 in which a positive electrode mixture sheet using nickel hydroxide, which has a more noble potential than zinc oxide, was placed instead of the negative electrode mixture sheet (B) (zinc oxide ion donor), the metallic zinc dendrites that had grown and reached the positive electrode mixture sheet lowered the potential of the positive electrode mixture sheet to the hydrogen generation potential, causing hydrogen gas to be generated from the positive electrode mixture sheet, and stable charging and discharging could not be performed.

[0144] In addition to the charge-discharge cycle test, the secondary batteries of Example 4 and Comparative Example 1 were tested under the same conditions as above except that the charge quantity of electricity (1) and the discharge quantity of electricity (5) were changed to 480 mAh, respectively, and an accelerated test was performed to evaluate the charge-discharge cycle characteristics.

[0145] The measured discharge capacity of each battery is shown in FIG. 10, which is expressed as a relative value with the initial discharge capacity taken as 100.

[0146] As shown in FIG. 10, even in the secondary battery of Example 4 in which the content of zinc oxide per unit area in the zincate ion donor was reduced to ¼ of that in the secondary battery of Example 1, the occurrence of short circuits due to passivation of the negative electrode and dendrite formation could be suppressed, and the charge-discharge cycle characteristics could be improved. [Explanation of symbols]

[0147] 1. Laminate of negative electrode, insulating layer and zincate ion donor 2 negative electrode 21 Negative electrode mixture layer [Layer (A) made of negative electrode mixture sheet] 22 Current collector 23 Current extraction section 3 Zinc oxide ion donor [layer (B) made of negative electrode mixture sheet] 4. Insulation Layer 5 Positive electrode

Claims

1. A secondary battery having a negative electrode containing zinc oxide, a positive electrode, and an alkaline electrolyte, a layered zincate ion donor containing zinc oxide or zinc hydroxide is provided between the negative electrode and the positive electrode; A secondary battery, characterized in that the zincate ion donor is not conductively connected to either the negative electrode or the positive electrode.

2. 2. The secondary battery according to claim 1, further comprising a separator between the zincate ion donor and the positive electrode.

3. Between the zincate ion donor and the negative electrode, the basis weight is 50 g / m 2 3. The secondary battery according to claim 1, further comprising a porous layer containing the nonwoven fabric or insulating particles.

4. The secondary battery according to any one of claims 1 to 3, wherein the total content per unit area of ​​zinc oxide and zinc hydroxide in the zincate ion donor is 10 to 300 mass % of the content per unit area of ​​zinc oxide in the negative electrode.

Citation Information

Patent Citations

  • JP1973036640A

  • Image transmitter, image processing device, and image transmission and reception system

    JP2006074541A

  • electrode

    JP2008537302A

  • Secondary battery

    JP2009093983A

  • Secondary battery

    JP2014222570A